Atypical presentation of biliary ileus: individualized surgical approach. Case report - Rivadeneira-Proaño , Francisco (2025)
Introduction: Biliary ileus, representing less than 0.5% of intestinal obstructions, arises as an uncommon complication of cholelithiasis. This condition originates from biliary-enteric fistulas, mainly cholecystoduodenal, and its diagnosis often poses challenges due to nonspecific clinical manifestations. Objective: To describe a case of biliary ileus with an atypical presentation and analyze the individualized surgical approach employed, highlighting the criteria used for decision-making and its impact on managing intestinal obstruction. Case Presentation: The patient presented with an insidious clinical course characterized by abdominal pain, vomiting, and weight loss, leading to an extensive exploratory laparoscopy that resulted in an enterolithotomy to address the obstruction. Discussion: The Mordor triad, along with imaging studies such as computed tomography, aids in the diagnosis, although it is often confirmed during surgery. The standard surgical management, whether laparotomy or laparoscopy, is adapted according to the patient's risk, with either one- or two-phase approaches. Conclusion: Biliary ileus, though rare, requires prompt recognition and personalized surgical intervention. The absence of a uniform approach underscores the need for individualized decisions based on surgical risk, recurrence, and associated mortality.